THE EXPRESSIONS OF FREEDOM AND RESISTANCE IN GUNS N’ ROSES’ APPETITE FOR DESTRUCTION - Nizarur Rahman; Nur Saktiningrum (Universitas Gadjah Mada, 2019)
Music and song lyrics are artistic works for people from any social group to listen to and read. Song lyrics have been situated in various social contexts. Social realities or circumstances, for example, have often been the source of inspiration for song lyrics. This kind of social aspect is apparent in Guns N’ Roses’ album Appetite for Destruction. The album presents songs with lyrics that portray various social and cultural issues in contemporary society. Through the stories of survival from the physical and mental abuse since childhood, the portrayal of those issues represents the freedom of expression and resistance. Freedom and resistance are a response to abusive behavior and social establishment. This kind of response represents the attitude demonstrated by subculture groups. The present article studies the song lyrics in Appetite for Destruction with the above mentioned topic. The topic is discussed using John Rowe’s postnationalist approach and analyzed using Charles Sanders Peirce’s semiotic method. The discussion also draws on the concept of subculture as described by Dick Hebdigie. The primary data are the words and sentences in the album that signify expressions of freedom and resistance. The study led to the finding that the album reveals freedom and resistance from the perspective of the victims of physical and mental abuse since childhood. The spirit of freedom and resistance is their anchor throughout their survival from abuses and pitfalls in society. It also found that the song lyrics describe the social realities of subculture groups with the same spirit in surviving life predicaments and the social establishment.Keywords: song lyrics; resistance; expression of freedom; abuse; Appetite for Destruction